2015
DOI: 10.1007/s00420-015-1073-7
|View full text |Cite
|
Sign up to set email alerts
|

Practical on-site measurement of heat strain with the use of a perceptual strain index

Abstract: The PeSI is a simple, robust, reliable, and user-friendly tool for heat strain assessment in occupational settings. The perceptual strain zone will provide practical guidelines for on-site heat strain monitoring for construction workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Most of the construction activities observed were judged to require moderate or high workloads according to the reference table in the ACGIH guidelines (ACGIH, 2009). This is consistent with what has been perceived and described by construction workers (Chan and Yang, 2016; Venugopal et al , 2016) and confirmed by observation and measurement (Abdelhamid and Everett, 2002; Maiti, 2008; Rowlinson and Jia, 2014; Chinnadurai and Venugopal, 2016; Meade et al , 2016; Roja et al , 2016). Workers were determined to work far beyond the time allowed by the ACGIH TLV throughout their work shift, particularly outdoors and when performing heavy work activities indoors.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the construction activities observed were judged to require moderate or high workloads according to the reference table in the ACGIH guidelines (ACGIH, 2009). This is consistent with what has been perceived and described by construction workers (Chan and Yang, 2016; Venugopal et al , 2016) and confirmed by observation and measurement (Abdelhamid and Everett, 2002; Maiti, 2008; Rowlinson and Jia, 2014; Chinnadurai and Venugopal, 2016; Meade et al , 2016; Roja et al , 2016). Workers were determined to work far beyond the time allowed by the ACGIH TLV throughout their work shift, particularly outdoors and when performing heavy work activities indoors.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, even if we consider these possible biases, we can still conclude that climate-change mitigation is indispensable for minimizing the climate-change impacts, regardless of the implementation of working time shift. Moreover, a larger portion of economic loss is caused by the construction sector (Figure 6b), and the current working time in the construction sector is not as early as that of the agricultural sector (Bates et al, 2010;Bodin et al, 2016;Chan & Yang, 2016;Chan et al, 2017;Crowe et al, 2010Crowe et al, , 2013Delgado Cortez, 2009;Hassan et al, 2017;Inaba & Mirbod, 2007;Ioannou et al, 2017;Maiti, 2008;Meade et al, 2017Meade et al, , 2015Miller et al, 2011;Sahu et al, 2013;Vatani et al, 2016, summarized in Table S4). In the sensitivity analysis, up to 3 hr of shift was assumed during the base period for the construction sector as well as the agricultural sectors.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the PeSI shares a moderate relationship (r = 0.77; p < 0.001) with the PSI when wearing heavy (~34 kg) personal protective clothing across a range of environments and metabolic workloads [7]. Several other studies have demonstrated the ability of the userfriendly PeSI to predict physiological strain across clothing types [6,[8][9][10], operational scenarios [8,9,11] and in the field [10,12]. Further, the PeSI has shown the capacity to differentiate strain between activity [8] and fitness [6] levels.…”
Section: Introductionmentioning
confidence: 99%